Analysis of Categorical Subgroup Method for Resonance Self-Shielding Treatment - Li, Song; Zhang, Zhijian; Zhang, Qian; Hao, Chen; Zhao, Qiang (Frontiers in Energy Research, 2019)
To meet the requirements of one step lattice calculation on resonance effect, a self-developed design and construction of a resonance treatment code are composed based on subgroup method and HELIOS-1.11 library. Subgroup fixed source equations are solved by method of characteristics to get subgroup fluxes, which are subsequently used to deduce effective resonance cross sections combined with subgroup weights and subgroup levels. Bondarenko method is employed to handle resonance interference effect and a resonance category scheme and resonance geometry simplification method are introduced to improve efficiency. Benchmarks of single pin cells and assemblies of light water reactor are adopted for numerical validation and the calculating results indicate that this method can treat resonance effect both precisely and effectively.